PEMBERDAYAAN GENERASI MUDA DESA MELALUI EDUKASI BAHAYA NARKOBA DAN JUDI ONLINE DALAM PROGRAM PERGURUAN TINGGI GOTONG ROYONG - Nurmaesah, Nunung; Lincawati, Iin; Wildan, M.; Hidayat, Syamsul; Kusuma, Jaka Wijaya; Sulaeman, Yeni (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Introduction: Narcotics are substances or drugs that are both natural, synthetic, and semi-synthetic that cause the effects of decreased consciousness, hallucinations, and arousal, these illegal drugs can trigger various harmful impacts on health. Drug abuse can lead to memory loss to death. Online gambling is a game that is usually in the form of cards in an application or website. Through this game, players put money collateral to be used as betting material and hope to get a lot of profit. Although tempting, playing online gambling has a big impact that players often do not realize. Objective: Community Service Activities (PKM) aim to help increase knowledge about the side effects of drug use and online gambling. Method: This PKM is carried out by providing counseling education using an approach to students with a total of 94 respondents ResultThe level of knowledge about drugs and online gambling before being given education was in the good to less good category, but after being given education and a post-test, it increased to be better than before. Conclusion: After being given education, the respondents' level of knowledge increased to become better